Keith Richard Gooderham. (4th January 2020) - Bradbury, Janet; Cook, Jane; Cserep, Tibor; Jones, Trevor; Lister, Stephen; McMullin, Paul; Shirley, Martin; Turk, Mike
Abstract : A vet with a special interest in ducks who used his diagnostic abilities, problem‐solving skills and a common‐sense approach to improve bird health and welfare.